2020
DOI: 10.1093/cdn/nzaa105
|View full text |Cite
|
Sign up to set email alerts
|

Association of DHA Concentration in Human Breast Milk with Maternal Diet and Use of Supplements: A Cross-Sectional Analysis of Data from the Japanese Human Milk Study Cohort

Abstract: ABSTRACT Background DHA (22:6n–3) is essential for neurodevelopment in children, and its concentration in human breast milk is historically high in Japan. Dietary patterns in Japan might affect the fatty acid (FA) composition among lactating mothers. Objectives Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 32 publications
0
23
1
Order By: Relevance
“…Open access contributed to various aspects of the literature regarding human milk composition. [31][32][33][34] Osteopontin (OPN) concentration in human milk OPN is a multifunctional protein that is present in various cells, tissues and body fluids. 35 36 Its concentration is the highest in milk and is significantly higher in humans than in cows.…”
Section: Human Milk Macronutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Open access contributed to various aspects of the literature regarding human milk composition. [31][32][33][34] Osteopontin (OPN) concentration in human milk OPN is a multifunctional protein that is present in various cells, tissues and body fluids. 35 36 Its concentration is the highest in milk and is significantly higher in humans than in cows.…”
Section: Human Milk Macronutrientsmentioning
confidence: 99%
“…32 A multivariate linear regression model showed an association between DHA concentration in human milk and maternal dietary intake of grilled fish, which is the most common method of cooking seafood in Japan, after adjustment for DHA supplementation use, maternal and infant age, maternal BMI and infant birth weight. 32 These results will contribute to a better understanding of the FA composition in Japanese human milk. DHA concentrations in human milk in the present study were lower than those reported previously for Japanese samples (mean milk DHA concentration of 0.65% vs 0.99% 39 and 1.09% 40 ), which may reflect the reduced intake of fish in the Japanese population.…”
Section: Findings To Date From Thementioning
confidence: 99%
“…These premature infants are reliant on enteral sources of DHA, most commonly through breast milk [ 13 ]. However, the DHA content in breast milk varies in direct correlation with maternal DHA intake [ 14 , 15 , 16 ], and mothers consuming a Western diet have lower levels of DHA in their milk as commonly DHA intake is below the recommended minimal intake of 450 mg/day for pregnant and lactating women [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, our study suggests that supplementation with a probiotic mixture during lactation, but not during pregnancy, modified the cytokine profile in mature milk. As dietary supplements are already popular among lactating women in Asian countries, this study also provides a simple regimen for implementing probiotic supplementation [ 30 ], one that does not require administration of probiotics to the infants.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, mothers who chose the probiotic group were more concerned about their health, and their diets and lifestyles may have influenced the results. n -3 PUFA supplements including fish oil are becoming increasingly popular in pregnant and lactating women in Japan and other East Asian countries [ 30 ], and their usage may affect immune components in breast milk [ 36 ]. However, detailed information on diet was not obtained in this study.…”
Section: Discussionmentioning
confidence: 99%